Perkembangan Tafsir Al-Qur'an Kontemporer - Muhammad Irham; Muhammad Fikran Said; Rosmini (Jurnal Ilmu Agama Indonesia, 2026)
The development of contemporary Qur’anic interpretation constitutes an integral part of the intellectual dynamics of the Muslim community in responding to social change, cultural transformation, and the challenges of modernity. Qur’anic interpretation is no longer confined to literal textual understanding but has evolved toward contextual, critical, and multidisciplinary approaches. This article aims to examine the development of contemporary Qur’anic interpretation by focusing on contextual approaches, multidisciplinary methods, and socio-humanitarian orientations. This study employs a qualitative approach using a library research method. Data were collected from the works of contemporary Muslim exegetes and scholars, as well as relevant academic literature, and were analyzed using content analysis techniques. The findings indicate that contemporary Qur’anic interpretation has undergone a paradigm shift from textual approaches to contextual interpretations that are more responsive to social realities. This approach is supported by multidisciplinary methods that enable a more comprehensive and applicable understanding of the Qur’an. The socio-humanitarian orientation emerges as a central objective of contemporary interpretation in addressing issues of justice, public welfare, and humanity in the modern era. This study concludes that contemporary Qur’anic interpretation represents a methodological continuation of classical exegetical traditions aimed at maintaining the Qur’an’s relevance as a guiding source for human life across time.